Aspiration numérique et mise à distance du corps - Renaud Hétier (Recherches en Éducation)
Digital devices, being permanently available, authorizing ourselves to be linked with other connected users, alter our vision of time and space. Extended to the network level, this experiment finds its place in space, and, making every moment equally important, detemporalizes itself. As they allow an almost continual presence, digital devices ask for a permanent availability of our individual bodies. School, also impacted by this networking, strengthens its tendency towards individualization (each pupil being busy with its own tablet) and may not develop an ability of bound-together learning. The virtualization of present time, activity, violence is part of the humanization process as states Pierre Levy. But digital commitments of the young generation are to be analyzed on the game level, understood as a virtualization of the game (playing with language, playing with technique). This twofold mediation (game + virtualization) makes it easy to mix game and violence, the last being avoided by a deliberate distance and by fictionalization. As the borderline is not experienced (by destruction, by experiencing vulnerability), the necessity of an agreement virtualizing violence may not be felt. Indeed, not everything can be virtualized, and the body-to-body experiment needs to be anticipated to learn how to live together. The temptation of getting rid of one’s body (for a lighter life?) must be worked on. Moreover, school, thought as a space where to share one’s living, is a space (of working, of knowing) only when it is shared and inhabited.